2007
DOI: 10.3168/jds.2006-882
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Peripartum Mastitis in Pasture-Grazed Dairy Heifers

Abstract: A longitudinal observational field study was conducted using 708 heifers in 30 spring-calving dairy herds in the Waikato region of New Zealand. The aim of the study was to investigate risk factors for subclinical and clinical mastitis (CM) in the peripartum period using path analysis methods and to find the factors most important at the population level as a basis for potential control programs. Body condition and udder hygiene scores, blood samples, and quarter mammary secretion samples for bacteriology were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
3
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 21 publications
(26 reference statements)
3
49
3
1
Order By: Relevance
“…Prepartum IMI could be one of the risk factors for clinical and subclinical mastitis in heifers [8], and some studies indicated that IMI in unbred heifers could be associated with reduction in alveolar epithelial and luminal areas and increase in connective tissue stroma [6,29].…”
mentioning
confidence: 99%
“…Prepartum IMI could be one of the risk factors for clinical and subclinical mastitis in heifers [8], and some studies indicated that IMI in unbred heifers could be associated with reduction in alveolar epithelial and luminal areas and increase in connective tissue stroma [6,29].…”
mentioning
confidence: 99%
“…As reported, mastitis is found to be more predominant in Friesian breeds when compared to Jersey and Ayrshire heifers [13]. In general, the cows more than 10 years were prone to subclinical phase than the younger ones and which have calved more than seven had a greater chance for developing udder infections with more possibility for the mounting of clinical mastitis during the first 3 months of lactation [14,15].…”
Section: Discussionmentioning
confidence: 64%
“…In another study, cow cleanliness, udder cleanliness, and SCC scores were not different for docked heifers compared with intact heifers . No significant differences were observed in SCC, udder cleanliness, or intramammary infection between docked and intact cattle (Schreiner and Ruegg, 2002;Compton et al, 2007).…”
Section: Udder Healthmentioning
confidence: 92%